Pengaruh Brand Trust dan Harga Terhadap Keputusan Pembelian Pada Rumah Makan Kepiting Sari di Malang - Pedro Afdhol Fausta; Fullchis Nurtjahjani (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Business rivalry compels business owners to continuously seek effective strategies to maintain their market position. This challenge is also faced by Rumah Kepiting Sari, which strives to survive amidst competition by leveraging brand trust and price differentiation. This study aims to determine and analyze the influence of brand trust and price on consumer purchasing decisions. The research employs a quantitative approach using a non-probability sampling technique. Data were collected through questionnaires distributed to 100 respondents who had made a purchase decision at Rumah Kepiting Sari. The data were analyzed using multiple linear regression and hypothesis testing. The findings reveal that the brand trust variable has a significant positive effect on purchasing decisions, whereas the price variable does not significantly influence consumer purchasing behavior. However, when considered simultaneously, brand trust and price together have a significant effect on purchasing decisions. The coefficient of determination (R²) obtained in this study is 0.397, indicating that 39.7% of the variance in purchasing decisions can be explained by brand trust and price, while the remaining 60.3% is influenced by other factors not examined in this research. These results suggest that building and maintaining consumer trust in the brand is more impactful in influencing purchasing behavior compared to price considerations. Therefore, it is recommended that Rumah Kepiting Sari continues to enhance brand trust through consistent service quality, product reliability, and strong customer engagement, while also evaluating pricing strategies to remain competitive. Strengthening these aspects will contribute to long-term customer loyalty and sustainability in a competitive business environment.